Theoretical and experimental investigations of isosteric heats for water adsorption on silica gel surfaces - Fan, Wu (2020)
The knowledge of the isosteric heats (Qsto) is essential to design porous adsorbents for calculating the performances of adsorption-assisted cooling, separation and gas storage systems. This paper presents a thermodynamic framework to calculate the interaction potentials and isosteric heats for water adsorption on SiO2 structures. Here both Lennard Jones (LJ) and electrostatic potentials are considered. It is found that (i) Qsto varies from 1.37 eV (∼131 kJ/mol) to 0.54 eV (∼52 kJ/mol) for the adsorption of one water molecule on various pore sizes of SiO2 structure, and (ii) Qsto depends on the pore size (H). Qsto is found to be very high in the super-micro-pore regions. The density functional theory (DFT) is applied to calculate Qsto for the adsorption of water on silica. Here water-water interactions are not considered. Later Qsto for five types of silica gels are obtained from experimentally-measured isotherms data at low pressures (up to 0.15 kPa) and wide range of temperatures. The simulation result agrees well with the experimental data.